2022
DOI: 10.1093/ndt/gfac191
|View full text |Cite
|
Sign up to set email alerts
|

Inhibit progression of coronary artery calcification with vitamin K in hemodialysis patients (the iPACK-HD study): a randomized, placebo-controlled multi-center, pilot trial

Abstract: Background Vitamin K activates matrix Gla protein (MGP), a key inhibitor of vascular calcification. There is a high prevalence of sub-clinical vitamin K deficiency in patients with end stage kidney disease. Methods A parallel randomized placebo-controlled pilot trial designed to determine whether 10 mg of phylloquinone thrice weekly versus placebo modifies coronary artery calcification progression over 12 months in patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…We also found no difference in CAC prevalence or incidence across plasma (dp)ucMGP categories. Our results are generally consistent with the available recent evidence from vitamin K supplementation randomized controlled trials (RCTs), which collectively do not support a protective role for vitamin K supplementation in improving the vascular health of individuals with CKD [ [33] , [34] , [35] ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We also found no difference in CAC prevalence or incidence across plasma (dp)ucMGP categories. Our results are generally consistent with the available recent evidence from vitamin K supplementation randomized controlled trials (RCTs), which collectively do not support a protective role for vitamin K supplementation in improving the vascular health of individuals with CKD [ [33] , [34] , [35] ].…”
Section: Discussionsupporting
confidence: 87%
“…A trial conducted in adults with stage 3b-4 CKD found no effect of 400 μg/d menaquinone-7 (a form of vitamin K2) on arterial stiffness or other measures of vascular health over 1 y [34]. In a recently completed pilot RCT comprising individuals on hemodialysis with a baseline AS of ≥30 AU, phylloquinone supplementation (10 mg thrice weekly) showed no effect on CAC progression over 1 y [ 35 ]. Results of RCTs focused on arterial stiffness were similarly unconvincing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…125 As underpowered clinical randomized Vitamin K trials have shown divergent results, fully powered randomized trials should be initiated possibly combining vitamin K2 with a phosphate binder. [126][127][128][129] Mitochondrial Dysfunction-When Cells Run Out of Energy…”
Section: Risk Of Cardiovascular Complications In Chronic Kidney Diseasementioning
confidence: 99%
“…In all, the ten RCTs involved 733 patients, including 365 in interventional group and 367 in control groups. Among these studies, six were conducted in hemodialysis patients (13)(14)(15)(16)(17)(18)(19), two were conducted in non-dialysis CKD patients (20, 21), and one was conducted in kidney transplantation recipients (22). All studies were conducted in adult population, except for one study which had been conducted in pediatric population.…”
Section: Study Characteristicsmentioning
confidence: 99%